Analysis of the effects of topical renal hypothermia on lung tissue after kidney ischemia and reperfusion in rats - Fiorentini,Marlon Roberto (2015)
PURPOSE: To evaluate whether topical renal hypothermia (TRH) at different levels of temperature has protective effects on lung tissue after renal I/R, through an analysis of organ histology and inflammatory markers in lung tissue. METHODS: Twenty-eight male Wistar rats were randomly allocated across four groups and subjected to renal ischemia at different levels of topical renal temperature: normothermia (no cooling, 37°C), mild hypothermia (26°C), moderate hypothermia (15°C), and deep hypothermia (4°C). To induce I/R, the vessels supplying the left kidney of each animal were clamped for 40 minutes, followed by reperfusion. After four hours, another procedure was performed to harvest the tissues of interest. TNF-α, IL-1β and myeloperoxidase activity were measured in lung tissue. Histological analysis was performed in hematoxylin and eosin-stained lung specimens. RESULTS: Induction of renal I/R under deep topical hypothermia resulted in a significant decrease in lung concentrations of TNF-α compared with normothermic I/R (p<0.05). A trend toward significant correlation was found between lung IL-1β concentration and intensity of hypothermia (Spearman r=−0.37; p=0.055). No difference was found in myeloperoxidase activity or histologic injury between groups. CONCLUSION: Topical renal hypothermia reduces activation of the inflammatory cascade in the lung parenchyma. However, tissue-protective effects were not observed.